Deskripsi minat peserta didik dalam belajar matematika melalui permainan - Nurjaya, Nurjaya; Rahayu, Nina; Sari, Rita (Al-Azkiya: Jurnal Pendidikan MI/SD, 2023)
Math is one of the subjects that students dislike. Starting from the MI level even to college. Learners think that math is difficult, while math lessons themselves are applied in everyday life. This study aims to determine the efforts made by teachers in increasing students' interest in learning mathematics through games. The method used in this research is a literature review with the SLR (Systematic Literature Review) method, the research data source is a journal. The results of the analysis show that the game method can increase students' interest in learning mathematics, students feel learning is more fun, not burdened, and math is not boring anymore.